Limites institucionais e impactos sociais: a interrupção do projeto “IFSP: Conheça-nos!” - Giraldi, Gabriela do Prado (Universidade Federal de São Carlos, 2018)
The creation and strengthening of the Federal Institute of Education, Science and Technology of São Paulo are part of a package of developmental measures adopted for the implementation of public education policy. After a few years of implementation of the São João da Boa Vista Campus of the IFSP, it was noticed the need to strengthen its relationship with the local and regional community. Thus, the project "IFSP: Conheça-nos!" has been implemented from 2015 to 2016, which combines the university extension to public communication, in order to inform the services offered by the institution and to relate to its public. It happens that after two years fulfilling the objectives proposed and generating positive results, the mentioned project was interrupted. Therefore, the objective of this work is to identify the motivation of its end and its consequences, trying to propose ways for the continuity of the popularization actions of the school. This is because the discontinuity of the project activities suggests that institutional limits were decisive for its interruption. In order to fulfill the objectives, the present study structured through a bibliographical survey, documentary and secondary data analysis, as well as interviews with representative agents (project members) and participant observation, since the researcher was part of the team. Among societal, organizational and personal barriers, it can be said that all of them contributed in some way to the interruption of the project. However, organizational factors were preponderant to their discontinuity. Issues related to culture and the niches of power existing in the organization were the main cause of the team's discontinuance in persisting with the execution of the activities, thus revealing a serious problem of democratic school management. It can be concluded that the social consequences or impacts that result from this scenario is the perpetuation of a vicious cycle that keeps a public institution impervious to the interests of the community. Since there is no democratization of services, besides opening spaces for individualistic interests, the school institution fails to fulfill its transforming role in society, as provided for in its institutional and legal documents, thus reflecting the country's social development indicators. Finally, it is hoped that this work will contribute to the agenda of empirical research on the Federal Institutes of Education, Science and Technology, as well as on communication in public institutions, reflecting ideas and actions of the area that contribute to democratization of public education policy.
Institutional limits and social impacts: the interruption of the project "IFSP: Conheça-nos!"
Keywords: Desenvolvimento; Democratização da educação pública; Comunicação pública; Gestão democrática; Instituto Federal de São Paulo; Development; Democratization of public education; Public communication; Democratic management; Federal Institute of São Paulo; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA